2022
DOI: 10.5334/tohm.715
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evidence of Transcutaneous Afferent Patterned Stimulation for Essential Tremor

Abstract: Background: Transcutaneous afferent patterned stimulation (TAPS) is a prescription, wristworn device-delivered, non-invasive neuromodulation therapy for treatment of hand tremor in patients with essential tremor (ET). This retrospective post-market surveillance study evaluated real-world effectiveness of TAPS from patients using therapy on-demand for at least 90 days between August 2019 through June 2021.Methods: Demographics were summarized from TAPS prescriptions received from the patient's healthcare provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
4
7
0
Order By: Relevance
“…TAPS provided safe and effective relief of PD-associated action tremor, similar to results of previously reported relief of ET-associated action tremor [8][9][10][11]18], suggesting TAPS may be a valuable treatment option for both PD and ET patients with action tremor. Action tremor improvement was demonstrated across multiple 1 and 2 for MDS-UPDRS and BF-ADL ratings across all tasks and visits.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…TAPS provided safe and effective relief of PD-associated action tremor, similar to results of previously reported relief of ET-associated action tremor [8][9][10][11]18], suggesting TAPS may be a valuable treatment option for both PD and ET patients with action tremor. Action tremor improvement was demonstrated across multiple 1 and 2 for MDS-UPDRS and BF-ADL ratings across all tasks and visits.…”
Section: Discussionsupporting
confidence: 84%
“…While chronic stimulation of VIM with deep brain stimulation (DBS) has been used to relieve upper limb motor symptoms in both essential tremor (ET) and PD [ 15 16 ], and both ET and PD patients are prescribed propranolol for action tremor control [ 17 ], to date TAPS has only been evaluated in patients with ET. Studies demonstrating the efficacy and safety of TAPS in ET include three randomized clinical trials (two completed studies randomized to sham [ 8 9 ] and an active study randomized to standard-of-care ( clinicaltrials.gov NCT05540626)) as well as two longitudinal home-use studies [ 11 18 ]. This study sought to evaluate the use of TAPS in PD patients with action tremor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAPS devices were authorized by the U.S. Food and Drug Administration (DEN170028) for the treatment of essential tremor symptoms, recent label expansion includes both ET and postural and kinetic hand tremors in Parkinson's disease [17,18]. TAPS devices measure each patient's unique tremor signature and deliver alternating bursts of stimulation pulses to the median and radial nerves at each patient's tremor frequency [19][20][21][22]. Patients use TAPS to relieve tremor symptoms when needed, typically when patients' tremors are worse or in preparation for activities requiring hand control.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have demonstrated the effectiveness and safety of TAPS in open-label and shamcontrolled studies [19][20][21][22][23][24], randomized evidence with home use beyond in-office assessment or in comparison to standard of care remains lacking. The purpose of this study was to evaluate the clinical outcomes of adding TAPS to standard of care over a one-month period of home use.…”
Section: Introductionmentioning
confidence: 99%